Transneuronal Degeneration in the Brain During Glaucoma - You, Mengling; Rong, Rong; Zeng, Zhou; Xia, Xiaobo; Ji, Dan (Frontiers in Aging Neuroscience, 2021)
The death of retinal ganglion cells (RGCs) is a key factor in the pathophysiology of all types of glaucoma, but there is no complete mechanism to explain the pathogenesis of glaucoma. RGCs are a group of central nervous system (CNS) neurons whose soma are in the inner retina. The axons of RGCs form the optic nerve and converge at the optic chiasma; from there, they project to the visual cortex via the lateral geniculate nucleus (LGN). In recent years, there has been increased interest in the dysfunction and death of CNS and retinal neurons caused by transneuronal degeneration of RGCs, and the view that glaucoma is a widespread neurodegenerative disease involving CNS damage appears more and more frequently in the literature. In this review, we summarize the current knowledge of LGN and visual cortex neuron damage in glaucoma and possible mechanisms behind this damage. This synthesis presents an updated and expanded view of neuronal damage in glaucoma, and reveals new and potential targets for neuroprotection and treatment.